Good and bad death: Introduction - Seale, Clive; van der Geest, Sjaak (Social science & medicine (1982), 2004)
Introduces a collection of papers on the crosscultural variation in patterns of disease, demographic factors and cultural norms that influence the experience of death, dying and grieving. The idea for the collection arose from a workshop in the Netherlands in November 2000 on the same subject, participants at which included medical and other health sector workers, sociologists, anthropologists, epidemiologists and others. The essays in this collection strongly suggest that variations in the perception of good and bad death are not just freely chosen cultural differences but should be understood also in their structural, political and economic context. (Quotes from original text)